2018
DOI: 10.1099/jmm.0.000787
|View full text |Cite
|
Sign up to set email alerts
|

Bactibilia in women affected with diseases of the biliary tract and pancreas. A STROBE guidelines-adherent cross-sectional study in Southern Italy

Abstract: Gram-negative bacteria have been linked to a tumour-associated inflammatory status. In the last 30 years, the analysis of mortality rate in Italy for PHC and GBC shows an increasing and a decreasing trend, respectively. Although this study targeted only 53 patients and does not reflect the frequency of diagnosis in a Southern Italian population, the decrease in GBC may raise the suggestion ofnon-adherence to a Mediterranean diet that may have become more prevalent in Southern Italy since the 1990s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…Blood was collected according to the microbiological recommendations for the diagnosis of IE and sent to the microbiology laboratory of the Department of Sciences for Health Promotion and Mother-Child Care, where a BD Phoenix™ system (BD Diagnostic Systems, Sparks, MD) determined species identification as previously reported [1,[20][21]. More than two separate blood cultures positive for coagulase-negative Staphylococci and other organisms that do not cause endocarditis were taken into account to define the microorganism responsible of IE according to the major criteria for the diagnosis of IE (Duke criteria) [2].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood was collected according to the microbiological recommendations for the diagnosis of IE and sent to the microbiology laboratory of the Department of Sciences for Health Promotion and Mother-Child Care, where a BD Phoenix™ system (BD Diagnostic Systems, Sparks, MD) determined species identification as previously reported [1,[20][21]. More than two separate blood cultures positive for coagulase-negative Staphylococci and other organisms that do not cause endocarditis were taken into account to define the microorganism responsible of IE according to the major criteria for the diagnosis of IE (Duke criteria) [2].…”
Section: Methodsmentioning
confidence: 99%
“…The identification of multidrug-resistant (MDR) gram-negative bacilli and Candida spp. were performed as previously reported [20][21]. Serological tests for pathogens that are epidemiologically relevant in our geographic area (i.e., Brucella spp.)…”
Section: Methodsmentioning
confidence: 99%
“…are strongly and negatively associated with PHC. 356 Notably, patients with intraductal papillary mucinous neoplasms with high-grade dysplasia are characterized by high levels of IL-1β and intracystic bacteria that exhibit cooccurrence with abundant oral bacterial taxa, including F. nucleatum and Granulicatella adiacens, indicating the role of oral bacteria in cystic precursors to pancreatic cancer. 357 Indeed, as has been reported previously, unsatisfactory oral health conditions, pathogenic oral microbiomes (such as Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans), periodontitis, and tooth dislocation are correlated with a higher risk of pancreatic cancer.…”
Section: Zhang Et Almentioning
confidence: 99%
“…The human intestinal microbes comprise numerous micro-organisms that can influence the host immunity and cancer conditions because gut microbes and the immune system are mutually affected via metabolic crosstalk. A researcher surprisingly discovered that PC is strongly correlated with Gram-negative gamma-proteobacteria-(GP-) Escherichia coli (E. coli) [3]. Moreover, Geller et al have demonstrated that GP can induce chemoresistance of Gemcitabine (Gem, the first-line drug of chemotherapy for PC patients) in PC patients by metabolizing Gem into an ineffective form, providing that gut bacteria contribute to worse outcomes of PC patients by making chemotherapeutic drug invalid [4].…”
Section: Introductionmentioning
confidence: 99%
“…Venn diagram DEGs were selected with P < 0:01 and fold change > 2 among the mRNA expression profiling sets GSE27890, GSE46234, and GSE107610. A total of 84 overlapping genes were obtained 3. BioMed Research International concluded that the gut bacteria can modulate tumor bacteria composition to regulate the progression of PC and the survival rate of PC patients.…”
mentioning
confidence: 99%